Initial Characterization of Activated Charcoal from the Indigenous Ziziphus mauritiana Wood from Dryland of Sumbawa - Lalu Heri Rizaldi; Ariskanopitasari; Nurman Muda Nasution; Widya Indriani; Ihlana Nairfana; Aluh Nikmatullah; Hery Haryanto; Muhammad Sarjan (Fakultas Teknologi Pangan & Agroindustri (Fatepa) Universitas Mataram dan Perhimpunan Teknik Pertanian (PERTETA), 2023)
Ziziphus mauritiana is widely found in Sumbawa arid and semi-arid area. It is a drought tolerant plant which grows in areas with extreme conditions. While information of the utilisation of Bidara seeds as activated carbon is available, there are limited resources that use Bidara woods. Therefore, this study aims to characterize the activated charcoal derived from Z. mauritiana wood which was activated using 25%, 30% and 35% of H2SO4 and NaOH. The moisture content, ash content, volatile matter, fixed carbon, and iodine absorption capacity were investigated and compared to the Indonesian National Standard (SNI. 06-3730-1995). The result showed that NaOH activated charcoal obtained higher quality compared to the H2SO4 activated charcoal. The best activated charcoal was obtained from 35% of NaOH which has 1.19% moisture content, 13.21% ash content, 1.42% volatile matter, 84.73% fixed carbon, and 1892.40 mg/g iodine number. This study concludes that the characteristics of Z. mauritiana activated charcoal (except the ash content) comply with Indonesian National Standard and potentially can be developed as an adsorbent.